A REVIEW OF ANALYTICAL MODELS OF STRAY RADIATION EXPOSURES FROM PHOTON- AND PROTON-BEAM RADIOTHERAPIES. Issue 1 (21st November 2017) - Newhauser, W D; Schneider, C; Wilson, L; Shrestha, S; Donahue, W
Abstract: External-beam radiation therapy is safe, effective and widely used to treat cancer. With 5-year cancer survival for adults above 70%, increasingly research is focusing on quantifying and reducing treatment-related morbidity. Reducing exposures to healthy tissues is one strategy, which can be accomplished with advanced-technology radiotherapies, such as intensity-modulated photon therapy and proton therapy. Both of these modalities provide good conformation of the therapeutic dose to the tumor volume, but they also deliver stray radiation to the whole body that increases the risk of radiogenic second cancers. To minimize these risks, one needs to create and compare candidate treatment plans that explicitly take into account these risks. Currently, clinical practice does not include routine calculation of stray radiation exposure and, consequently, the assessment of corresponding risks is difficult. In this article, we review recent progress toward stray dose algorithms that are suitable for large-scale clinical use. In particular, we emphasize the current state of physics-based dose algorithms for intensity-modulated photon radiotherapy and proton therapy.